Video directly observed therapy for tuberculosis in Malaysia: Early insights from a multicentre proof-of-concept initiative - Larry E Nyanti; Afzaninawati S Yusof; Michelle Goroh; Nur Akmanidar Zainudin; Nadiah Kamsani; Sarah Jane JC Chan; Kui Choon Yong; V Paranthaman; Vincent HZ Lee; Nuratika S Masimin; Saravanan Jayaraman; Thevadarshani Perpakaran; et al. (ResearchGate, 2023)
Conventional in-person DOTS is often inconvenient, while virtual directlyobserved therapy improves adherence and bacteriological resolution. 1,2 • Virtual DOTS can be synchronous or asynchronous – of the two, asynchronous V-DOTS (AVDOTS) is believed to be more convenient due to flexibility in timing (daily video submission and review can occur at different times in a day). • The Angsana AVDOTS platform (i) outsources DOTS to independent observers, reducing burden on government facilities, and (ii) is available daily, including weekends and public holidays • The objectives of this proof-of-concept initiative were: • Primary: assess technical and patient-related barriers to AVDOTS • Secondary: assess treatment adherence & completion rates under AVDOTS